Fundamentals of Glycosylation - Raghav, Alok; Ahmad, Jamal (IntechOpen, 2022)
The diverse phenomenon of post-translational modifications of biological macromolecules (proteins, lipids, and nucleic acids) includes phosphorylation, glycosylation, ubiquitination, nitrosylation, methylation, acetylation, lipidation, and proteolysis. The mechanism of protein glycosylation has an important role in the regulation of human health. This book identifies the fundamentals of glycosylation that help in understanding the concepts of protein glycosylation and its significance.